Ultrafast dye regeneration in a core–shell NiO–dye–TiO2 mesoporous film. Issue 1 (6th December 2017) - Tian, Lei; Föhlinger, Jens; Pati, Palas Baran; Zhang, Zhibin; Lin, Junzhong; Yang, Wenxing; Johansson, Malin; Kubart, Tomas; Sun, Junliang; Boschloo, Gerrit; Hammarström, Leif; Tian, Haining
Abstract : Ultrafast dye regeneration within 500 fs was monitored in a dye sensitized NiO–TiO2 core–shell electrode. Abstract : In this study, a core–shell NiO–dye–TiO2 mesoporous film was fabricated for the first time, utilizing atomic layer deposition technique and a newly designed triphenylamine dye. The structure of the film was confirmed by SEM, TEM, and EDX. Excitation of the dye led to efficient and fast charge separation, by hole injection into NiO, followed by an unprecedentedly fast dye regeneration ( t 1/2 ≤ 500 fs) by electron transfer to TiO2 . The resulting charge separated state showed a pronounced transient absorption spectrum caused by the Stark effect, and no significant decay was found within 1.9 ns. This indicates that charge recombination between NiO and TiO2 is much slower than that between the NiO and the reduced dye in the absence of the TiO2 layer ( t 1/2 ≈ 100 ps).